State policy of Ukraine in the field of patriotic education of youth: current state and prospects for development - Skrypniuk Оleksandr; Zhovnirchyk, Yaroslav (Public Administration and Regional Development, 2023)
The article studies the theoretical foundations of the State policy of modern Ukraine in the sphere of patriotic education of youth and provides practical recommendations for its improvement. The relevance of the study of the State policy of Ukraine in the sphere of patriotic education of youth, its current status and prospects for development is substantiated. The latest research and publications on this topic are analysed. A theoretical analysis of the problem of patriotic education of youth in Ukraine is carried out, namely: the concepts of “patriotism” and “education” are considered in their interconnection and complementarity with each other; the main components of patriotic education of youth are modelled and described in the form of a scheme; the role of the State in the patriotic education of modern youth is determined; the legislation of Ukraine in the field of patriotic education of youth is analysed; patriotic education of youth as a component of the State policy of Ukraine is considered. The current state of patriotic education of youth in Ukraine is studied, namely: the practical implementation of the state policy in the field of patriotic education of youth is analysed; the results of the activities of state and non-governmental organisations in the field of patriotic education of youth are assessed; the main problems and shortcomings in the current system of patriotic education of youth in Ukraine are identified. Prospects for the development of state policy in the field of patriotic education of youth are determined, namely: an analysis of the needs and challenges in patriotic education of youth in modern conditions is carried out; proposals for improving the state policy in the field of patriotic education of youth are provided; prospects for the development of patriotic education of youth in Ukraine are forecasted. Promising areas for further theoretical and practical research of the State policy of Ukraine in the field of patriotic education of youth are identified. Thus, the article is devoted to the study of the theoretical foundations and practical aspects of the State policy of Ukraine in the field of patriotic education of youth, including an analysis of the current state and prospects for development, as well as practical recommendations.